Excluding the marginalized? Exploring the livelihood and inequality implications of herbicide diffusion in eastern India - Mkondiwa, Maxwell; Krishna, Vijesh V.; Khed, Vijayalaxmi D. (International Maize and Wheat Improvement Center, 2023)
The increasing agricultural wages in rural India have lent significant R&D and policy support for laborsaving agricultural technologies. While some are heralded as ‘game changers’ in achieving food sufficiency goals, less research is devoted to understanding whether farmer adoption of these technologies worsens economic inequalities. We hypothesize that the rapid diffusion of laborsaving agricultural technologies could result in a reduction in employment and loss of a key source of livelihood for the nonfarming rural poor, especially women from socially marginalized groups. Analyzing two datasets (2,725 households) collected from the Bihar state of India in 2021– 22, we document empirical, stylized facts on the intersectionality of gender and caste on effects of a laborsaving technology—chemical weeding. We then develop a task-based conceptual framework in which social norms on tasks performed by women and marginalized caste groups are examined to understand the technology impacts on inequality. This framework helps in developing the relevant policy actions toward FROM RESEARCH TO IMPACT, October 2023 49 more inclusive innovation. We observe that herbicide adoption has increased by 50%age points in the past decade. A large share of the herbicide application labor is provided by male laborers replacing hand weeding labor, which is supplied mostly by female laborers from marginalized caste groups. Herbicide adoption has reduced the labor force participation of women from marginalized castes. We do not observe reinstitution of women hired laborers in other on-farm tasks (e.g., land preparation, sowing). There is no evidence of them getting better opportunities in the nonfarm sector or they have the necessary skillsets.